Free Cash Flow dan Profitabilitas terhadap Nilai Perusahaan dengan Retained Earnings to Total Assets sebagai Variabel Mediasi : Studi Empiris pada Perusahaan Sektor Properti dan Real Estate yang Terdaftar di Bursa Efek Indonesia - Jelita Mulia Dewi; Ario Purdianto; Agustina Agustina (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
This study aims to analyze the effect of free cash flow and profitability on firm value with Retained Earnings to Total Assets (RETA) as a mediating variable in property and real estate companies listed on the Indonesia Stock Exchange during the 2022–2024 period. This research employs a quantitative approach using secondary data obtained from companies’ financial statements. The sampling technique used is purposive sampling, resulting in 19 companies with a total of 57 observations. The data analysis method applied is panel data regression using the random effects model, along with regression-based mediation analysis conducted using STATA software. The results indicate that profitability has a positive and significant effect on firm value, suggesting that a company’s ability to generate profits is a key factor in increasing investor confidence. Meanwhile, free cash flow and RETA do not show a significant effect on firm value. Furthermore, RETA is not able to mediate the relationship between free cash flow and profitability on firm value. These findings imply that investors tend to place greater emphasis on direct profitability performance rather than retained earnings policies when evaluating firms in the property and real estate sector.